Adipose tissue may not be a major player in the inflammatory pathogenesis of Autism Spectrum Disorder - Baojiang Wang; Yueyuan Qin; Yong Chen; Xiujie Zheng; Yanjuan Chen; Juan Zhao; Feng Zhang; Shan Duan (Brain, Behavior, & Immunity - Health)
Purpose: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder increasingly recognized for its strong association with chronic inflammation. Adipose tissue functions as an endocrine organ and can secrete inflammatory cytokines to mediate inflammation. However, its involvement in ASD-related inflammation remains unclear. The present study aimed to clarify the role of adipose tissue in inducing inflammatory responses associated with ASD. Methods: A total of 36 children with ASD and 18 unrelated healthy controls, aged 2–14.5 years, were enrolled in the study. The up-regulated differentially expressed genes from the GSE18123 dataset were subjected to gene ontology (GO) enrichment analysis to explore ASD-associated pathways. Plasma cytokines and adipokines levels were quantified using Milliplex MAP immunoaffinity technology. The BTBR T + Itprtf/J (BTBR) mice that are known for their core ASD behavioral traits and inflammatory phenotypes were employed as an animal ASD model to verify the key clinical findings. Results: GO enrichment analyses revealed immune dysfunction in ASD. Symptom analysis showed that the recruited individuals had typical autistic symptoms. Plasma analysis showed no significant difference in adipokines levels, including adiponectin, leptin, resistin, adipsin, and lipocalin-2, between the ASD and control groups. However, markedly elevated levels of IL-6, IL-8, and tumor necrosis factor (TNF-α) were detected in children with ASD, suggesting that the inflammatory state is independent of adipokines. Similar results were also observed in BTBR autistic mice. Notably, levels of insulin, which are closely related to the exertion of adipokines function, also showed no significant changes. Conclusions: Our findings suggest that inflammation in ASD likely originates from non-adipocyte sources, implying that adipose tissue may not play a major role in inflammatory pathogenesis of ASD. Consequently, targeting adipose-related inflammation may not be an effective treatment approach, providing new directions for the development of targeted interventions.